Thermochemistry Comic as A Self Learning Resource for Grade 11 Students - Siska Oktapianti (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2021)
The purposes of this development research are: (1) to develop a chemistry comic book in thermochemistry chapter, (2) to evaluate quality of the chemistry comic book based on assessment of chemistry teachers and students at senior high school/islamic senior high school .This research uses procedural model that is a descriptive model. The procedural model contains many steps that we have to follow to launch a product. The development of this chemistry comic book is guided by thesis supervisors, media expert and peer reviewers. The instrument used to evaluate the quality of this chemistry comic book is a set of quality which has some aspects and criteria. The evaluation result is in qualitative data and then the result is tabulated and analyzed by the ideal evaluation criteria category guide to measure the quality of a chemistry comic book. This comic includes 5 sub topics, i.e heat, enthalpy and the change, calculating the change in enthalpy, calorimeter, and fuel. Based on the evaluation converted by 3 chemistry teachers and 6 students, the chemistry comic book developed in this research has a good quality. Based on teachers’ assessment, the chemistry comic book has a good quality, going the score of 146.33 from the maximum point 190 and ideal percentage 77.02%. Meanwhile, based on students’ assessment, it has a good quality, going the score of 106.33 from the maximum point 135 and ideal percentage 78.76%. There it can be used as the guideline of the additional study sources.